E-learning course: basis of harvest and preservation of tissues – design and initial experience - Měřička, Pavel; Štěrba, Lubomír; Straková, Hana; Navrátil, Pavel (Mefanet journal, 2014)
Background: The design and initial experience with the e-learning course “Basis of Harvest and Preservation of Tissues” used as a support of an elective subject is presented. The aim of the e-learning course was to enable the students to learn the theoretical principles of the subject individually and to present the gained knowledge at the final seminar. Methods: All functions of the course were operated in Moodle, local application of the Charles University in Prague, Faculty of Medicine in Hradec Králové. The course was divided into 3 main topics corresponding with topics of lectures: 1. Principles of tissue and organ donation, 2. Low temperature preservation of cells, tissues and organs, 3. Quality and safety assurance in practice of tissue and procurement establishments. A test consisting of 5 questions selected randomly from the bank of questions followed each topic. If the student answers correctly at least 3 questions he is allowed to pass to the next topic. The fourth topic “Basic processes in the tissue establishment and principles of their validation” was added into the electronic version as a tool for repeating and improving of knowledge. The fifth topic was represented by a database for uploading theses presented by students at the final seminar. The final test consisted of 15 questions (5 ones from each basic topic). It was necessary to answer correctly at least 10 questions to receive a certificate of completing the course. Results: The course was put into operation during the summer term of the academic year 2012/2013. To the date 15 of September the total of 23 students enrolled (17, i.e. all students of the elective subject in the Czech version, 2 students of this subject in the English version, 2 postgraduate students and 2 medical doctors). All enrolled students used the course for on-line learning, downloading, or printing course study materials. All undergraduate students were obliged to use it for preparation, consultation and presentation of seminar theses, i.e. 10 minute Power Point presentations followed by 5 minute discussion. Verification of the course was planed during the summer term of the academic year 2013/2014. Conclusions: The first experience showed that the presented e-learning course could serve as a useful support of the elective subject “Basis of Harvest and Preservation of Tissues”. It substantially enlarged the choice of study materials that can be regularly updated, so that the students receive the newest information. It can be also attractive for students that are not enrolled in the elective subject because of its limited capacity (not more than 20 persons) The efficiency of such form of education is being a subject of further verification.
Keywords: školy lékařské; Online Systems; uchovávání tkání; odběr tkání a orgánů; Tissue Preservation; Tissue and Organ Harvesting; Schools, Medical; on-line systémy; Education, Distance; distanční studium